Cost-effectiveness of a non-pharmacological treatment vs. “care as usual” in day care centers for community-dwelling older people with cognitive impairment: results from the German randomized controlled DeTaMAKS-trial - Kathrin Steinbeisser; Larissa Schwarzkopf; Elmar Graessel; Hildegard Seidl (The European Journal of Health Economics, 2020)
Background: Cognitive impairment in older adults causes a high economic and societal burden. This study assesses the cost-effectiveness of the multicomponent, non-pharmacological MAKS treatment vs. “care as usual” in German day care centers (DCCs) for community-dwelling people with mild cognitive impairment (MCI) or mild to moderate dementia over 6~months. Methods The analysis was conducted from the societal perspective alongside the cluster-randomized controlled, multicenter, prospective DeTaMAKS-trial with waitlist group design. Outcomes were Mini-Mental Status Examination (MMSE) and Erlangen Test of Activities of Daily Living in Persons with Mild Dementia or Mild Cognitive Impairment (ETAM) of 433 individuals in 32 DCCs. Incremental differences in MMSE and ETAM were calculated via a Gaussian-distributed and incremental cost difference via a Gamma-distributed Generalized Linear Model. Cost-effectiveness was assessed via cost-effectiveness planes and cost-effectiveness acceptability curves (CEAC). Results At 6~months, MMSE (adjusted mean difference0.167em=0.167em0.92; 95% confidence interval (CI): 0.17~to~1.67; p0.167em=0.167em0.02) and ETAM (adjusted mean difference0.167em=0.167em1.00; CI: 0.14 to~1.85; p0.167em=0.167em0.02) were significantly better in the intervention group. The adjusted cost difference was -0.167em exteuro938.50 (CI: -0.167em2733.65 to 763.13; p0.167em=0.167em0.31). Given the CEAC, MAKS was cost-effective for 78.0% of MMSE and 77.4% for ETAM without a need for additional costs to payers. Conclusions MAKS is a cost-effective treatment to stabilize the ability to perform activities of daily living and cognitive abilities of people with MCI or mild to moderate dementia in German DCCs. Thus, MAKS should be implemented in DCCs.
Keywords: I12 Health Behavior; 610; Dementia; MCI; Cost-effectiveness analysis; MMSE; ETAM; Non-pharmacological treatment